Continental Scientific Drilling A Decade of Progress, and Challenges for the Future - Harms, Ulrich; Koeberl, Christian; Zoback, Mark D. (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Scientific drilling is an indispensable tool of modern Earth science - search, as it provides the only means of obtaining direct information on processes operating at depth. Drilling allows for the determination of - situ properties of solid materials and fluids and permits testing of hypot- ses and models derived from surface observations. In addition, drill holes may be used as a natural laboratory for experiments and as observatories for long-term monitoring of on-going active processes. Earth drilling, therefore, plays a critical role in scientific research directed towards - proved understanding of the workings of our planet and has a key role in solving urgent socio-economic problems. As a rule, drilling projects are an integral component of major geosci- tific research programs, comprising comprehensive pre-site investigations, accompanying laboratory studies, the drilling phase itself, and consecutive measurements and tests in the drill hole. Such drilling programs are costly and thus only realizable to a limited extent. International cost sharing, the optimal utilization of all available resources, the incorporation of inter- tional leading experts, and the application of the existing know-how, as well as the selection of an optimal drilling location ("World Geological Site"), are thus essential elements of an international scientific drilling p- gram.